The use of social media as a source of nutrition information - Megan Kreft; Brittany Smith; Daniella Hopwood; Renee Blaauw (The South African Journal of Clinical Nutrition, 2023)
Introduction: There is an increase in young people’s engagement with social media (SM), specifically nutrition information. Nutrition misinformation is, however, prevalent on SM due to lack of professional gatekeeping of this user-generated content. Objectives: The study aimed to assess the use of SM as a platform for obtaining nutrition information and how the accuracy thereof is evaluated. Design: A descriptive cross-sectional study with an analytical component was conducted. Data were collected from 2 318 participants using a content- and face-validated self-administered online questionnaire. Descriptive statistics and relevant inferential statistics were used. A p < 0.05 indicates statistical significance. Setting: The survey was completed by students from Stellenbosch University, South Africa. Subjects: Undergraduate students (18–25 years) registered at Stellenbosch University (2021), South Africa (n = 2 318). Results: Of 2 318 participants (69% female), 1 615 used SM to access nutrition information, with YouTube being the most used platform for this purpose (96%). Females used SM significantly more than males (p < 0.001) and participants living in shared accommodation used SM significantly less than those in other living arrangements (p < 0.001). A minority (17%) of participants ‘actively’ turn to SM for nutrition information, while the majority (54%) engaged only if it happened to appear on their feed. The preferred nutrition content was ‘what to eat in a day’ (83%). Participants felt most comfortable following a registered dietitian (64%) for accurate nutrition information. Relatability (87%) was a characteristic that motivated participants to follow SM influencers and 16% trusted claims from health influencers on SM. Although 91% understood what evidence-based nutrition information means, 77% of participants struggled to determine the accuracy of nutrition information on SM, with females indicating significantly more difficulty than males (chi2 = 39, p < 0.001). Conclusion: The participants engaged with nutrition information on SM and understood what evidenced-based nutrition information is. However, the majority lack skill in determining information accuracy on SM. A dietitian was trusted most as a source of nutrition information.